Independent mobility of proteins and lipids in the plasma membrane of Escherichia coli. Issue 5 (30th April 2014) - Nenninger, Anja; Mastroianni, Giulia; Robson, Alexander; Lenn, Tchern; Xue, Quan; Leake, Mark C.; Mullineaux, Conrad W.
Summary Fluidity is essential for many biological membrane functions. The basis for understanding membrane structure remains the classic Singer‐Nicolson model, in which proteins are embedded within a fluid lipid bilayer and able to diffuse laterally within a sea of lipid. Here we report lipid and protein diffusion in the plasma membrane of live cells of the bacterium Escherichia coli, using Fluorescence Recovery after Photobleaching (FRAP) and Total Internal Reflection Fluorescence (TIRF) microscopy to measure lateral diffusion coefficients. Lipid and protein mobility within the membrane were probed by visualizing an artificial fluorescent lipid and a simple model membrane protein consisting of a single membrane‐spanning alpha‐helix with a Green Fluorescent Protein (GFP) tag on the cytoplasmic side. The effective viscosity of the lipid bilayer is strongly temperature‐dependent, as indicated by changes in the lipid diffusion coefficient. Surprisingly, the mobility of the model protein was unaffected by changes in the effective viscosity of the bulk lipid, and TIRF microscopy indicates that it clusters in segregated, mobile domains. We suggest that this segregation profoundly influences the physical behaviour of the protein in the membrane, with strong implications for bacterial membrane function and bacterial physiology.